Inflammatory Pathophysiology as a Contributor to Myeloproliferative Neoplasms - Fisher, Daniel Arthur Corpuz; Fowles, Jared Scott; Zhou, Amy; Oh, Stephen Tracy (Frontiers in Immunology, 2021)
Myeloid neoplasms, including acute myeloid leukemia (AML), myeloproliferative neoplasms (MPNs), and myelodysplastic syndromes (MDS), feature clonal dominance and remodeling of the bone marrow niche in a manner that promotes malignant over non-malignant hematopoiesis. This take-over of hematopoiesis by the malignant clone is hypothesized to include hyperactivation of inflammatory signaling and overproduction of inflammatory cytokines. In the Ph-negative MPNs, inflammatory cytokines are considered to be responsible for a highly deleterious pathophysiologic process: the phenotypic transformation of polycythemia vera (PV) or essential thrombocythemia (ET) to secondary myelofibrosis (MF), and the equivalent emergence of primary myelofibrosis (PMF). Bone marrow fibrosis itself is thought to be mediated heavily by the cytokine TGF-, and possibly other cytokines produced as a result of hyperactivated JAK2 kinase in the malignant clone. MF also features extramedullary hematopoiesis and progression to bone marrow failure, both of which may be mediated in part by responses to cytokines. In MF, elevated levels of individual cytokines in plasma are adverse prognostic indicators: elevated IL-8/CXCL8, in particular, predicts risk of transformation of MF to secondary AML (sAML). Tumor necrosis factor (TNF, also known as TNF alpha), may underlie malignant clonal dominance, based on results from mouse models. Human PV and ET, as well as MF, harbor overproduction of multiple cytokines, above what is observed in normal aging, which can lead to cellular signaling abnormalities separate from those directly mediated by hyperactivated JAK2 or MPL kinases. Evidence that NFkB pathway signaling is frequently hyperactivated in a pan-hematopoietic pattern in MPNs, including in cells outside the malignant clone, emphasizes that MPNs are pan-hematopoietic diseases, which remodel the bone marrow milieu to favor persistence of the malignancy. Clinical evidence that JAK2 inhibition by ruxolitinib in MF neither reliably reduces malignant clonal burden nor eliminates cytokine elevations, suggests targeting cytokine mediated signaling as a therapeutic strategy, which is being pursued in new clinical trials. Greater knowledge of inflammatory pathophysiology in MPNs can therefore contribute to the development of more effective therapy.